Waterproof, sebum-resistant and sweat-resistant pressure-sensitive double-sided adhesive tape and preparation method thereof

By adding specific ingredients to the adhesive and depositing fluorinated silica and nanotitanium fluoride films on the surface of the film, a nano-scale hydrophobic coating is formed, which solves the swelling and layering of traditional adhesive tapes in sweat, sebum and daily chemicals, and achieves efficient waterproof and durable adhesive properties.

CN119662142APending Publication Date: 2025-03-21XINFENG JIELI ELECTRICAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411614753.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

When traditional adhesive tapes are exposed to sweat, sebum and other daily chemicals for a long time, they are prone to swelling and layering, resulting in reduced or failure of adhesive performance, affecting the sealing and service life of handheld electronic devices and wearable devices.

Method used

A pressure-sensitive double-sided adhesive tape that is waterproof, sebum-resistant and sweat-resistant is adopted. By adding nanoboronitride microspheres, anti-ultraviolet stabilizers, silane-encapsulated cadmium oxide nanofillers, fluorinated polyurethane acrylate copolymers and other components to the adhesive, and depositing fluorinated silica and nanotitanium fluoride films on the outer surface of the upper release film and the lower release film to form a nano-scale hydrophobic coating.

Benefits of technology

It significantly enhances the resistance of the adhesive tape to sweat and sebum, reduces swelling and layering, extends the bonding service life of the equipment, and provides efficient waterproofing, ensuring that the product maintains stable sealing and bonding performance during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a waterproof, sebum-resistant and sweat-resistant pressure-sensitive double-sided adhesive tape and a preparation method thereof. Relates to the field of handheld electronic product packaging. According to the scheme, the nano boron nitride microspheres and the anti-ultraviolet stabilizer are added into the adhesive, so that the tolerance of the double-sided adhesive tape to sweat and sebum is remarkably enhanced, the swelling and layering phenomena of the adhesive tape caused by long-term contact with human secretions are reduced, and the bonding service life of equipment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of handheld electronic product packaging, specifically a waterproof, sebum-resistant, sweat-resistant pressure-sensitive double-sided adhesive tape and a preparation method thereof. Background Art

[0002] As people's demand for miniaturization and thinness of electronic products increases, traditional fixing and sealing methods (such as screws and gaskets) can no longer meet the use requirements of modern equipment due to their large size and complex operation. Therefore, lighter and easier to operate pressure-sensitive adhesive tapes have been widely used, especially in the bonding and sealing of the shell structure of handheld electronic devices and wearable electronic products. However, handheld electronic devices and wearable devices often come into long-term contact with sweat and sebum secreted by the human body during daily use, and even occasionally come into contact with substances such as water, food, beverages and cosmetics. These substances may contain acids, alkalis and greases, which pose a severe test to the structure and bonding properties of adhesive tapes;

[0003] Traditional adhesive tapes are prone to swelling and delamination when in contact with sweat, sebum and other daily chemicals for a long time, resulting in reduced adhesive performance or even failure, which may in turn cause the sealing of the housing of handheld electronic devices and wearable devices to fail, affecting the service life and performance of the product. Summary of the invention

[0004] The purpose of this application is to provide a technical solution to solve the problems raised in the above background technology.

[0005] To achieve the above objectives, this application provides the following technical solutions:

[0006] A method for preparing a waterproof, sebum-resistant, and sweat-resistant pressure-sensitive double-sided adhesive tape comprises the following steps:

[0007] (1) Lay the upper release film of polyethylene PE or polypropylene PP with a thickness of 10-15 μm on the working surface of the coating machine;

[0008] (2) adding 15-20 parts by mass of a modified epoxy acrylate copolymer, 5-8 parts by mass of a nano boron nitride microsphere filler, 5-10 parts by mass of a silane-encapsulated cadmium oxide nanofiller, 0.2 parts by mass of an anti-ultraviolet stabilizer, and 0.05 parts by mass of a nano silver ion antibacterial agent to a reaction kettle, stirring evenly, heating to 130° C. to 140° C., and gradually increasing the speed to 800 rpm for high shear mixing at 500 rpm for 30 minutes to obtain an upper adhesive mixture; coating the upper adhesive mixture on an upper release film to form an upper adhesive layer with a coating thickness of 8-12 μm; and then pre-drying at 80° C. for 10-20 minutes, secondary drying at 100° C. for 15-35 minutes, and final drying at 120° C. for 20-40 minutes in sequence;

[0009] (3) preparing a fluorinated polyester F-PET support film layer with a thickness of 6-8 μm, uniformly distributing 5-8 parts of tetraethyl lead-wrapped microsphere filler in the support film layer by high shear stirring, and then performing fluorination pretreatment and nano-scale corona treatment on the surface of the support film layer, and then superimposing it on the surface of the upper adhesive layer;

[0010] (4) adding 15-20 parts by mass of fluorinated polyurethane acrylate copolymer, 10-15 parts of encapsulated thallium oxide microsphere filler, 0.1 parts of antioxidant, and 0.2 parts of fluorinated polydimethylsiloxane to a reaction kettle and stirring for 15 minutes, and uniformly dispersing at 1000 rpm for 40 minutes to obtain a lower adhesive mixture; uniformly coating the lower adhesive mixture on the lower surface of the support film layer to form a lower adhesive layer with a thickness of 10-15 μm; and then pre-drying at 80° C. for 10-30 minutes, secondary drying at 90° C. for 15-45 minutes, and final drying at 100° C. for 20-60 minutes in sequence;

[0011] (5) Covering the surface of the lower adhesive layer with a polyethylene PE or polypropylene PP lower release film having a thickness of 10-15 μm;

[0012] (6) A fluorinated silicon dioxide film is deposited on the outer surfaces of the upper and lower release films of the tape using PECVD technology, and then a nano-titanium fluoride thin layer is deposited using plasma-assisted deposition; each layer is pre-dried at 70°C for 5 minutes after deposition, and finally dried at 150°C for 15 minutes to obtain a waterproof, sebum-resistant, and sweat-resistant pressure-sensitive double-sided adhesive tape.

[0013] Preferably, in step (2), the particle size of the silane-encapsulated cadmium oxide nanofiller is 20-30 nm, and the anti-ultraviolet stabilizer is Benzotriazole.

[0014] Preferably, in step (3), the support film layer is a composition of corona-treated fluorinated polyester F-PET and tetraethyl lead microsphere filler.

[0015] Preferably, in step (4), the particle size of the encapsulated thallium oxide microsphere filler is 10-20 nm, and the antioxidant is Hindered Amine Light Stabilizer.

[0016] Preferably, in step (4), the fluorinated polyurethane acrylate copolymer is also subjected to graded viscous drying treatment in sequence, including pre-drying at 45° C. for 5-15 minutes, drying at 60° C. for 10-30 minutes and setting drying at 80° C. for 15-45 minutes.

[0017] Preferably, in step (6), the thickness of the fluorinated silicon dioxide film deposited by PECVD is 80-120 nm, and the thickness of the nano-titanium fluoride thin layer is 5-8 nm.

[0018] A waterproof, sebum-resistant and sweat-resistant pressure-sensitive double-sided adhesive tape, the adhesive tape is composed of an upper release film, an upper adhesive layer, a PET film layer, a lower adhesive layer and a lower release film which are arranged in sequence.

[0019] In summary, the technical effects and advantages of the present invention are as follows:

[0020] 1. This solution significantly enhances the tolerance of double-sided adhesive tape to sweat and sebum by adding nano boron nitride microspheres and anti-ultraviolet stabilizers to the adhesive, reduces the swelling and delamination of the tape caused by long-term contact with human secretions, and extends the bonding service life of the equipment.

[0021] 2. The adhesive tape of this solution forms a nano-scale hydrophobic coating by depositing a fluorinated silicon dioxide film on the outer surface of the upper release film and the lower release film using PECVD technology, and depositing a thin layer of titanium fluoride by plasma assistance. This structure provides an efficient waterproof effect. Even in the case of short-term contact with water, the tape can still maintain good bonding strength to prevent external liquids from penetrating into the device.

[0022] 3. This solution uses nano-scale fluorinated silicon dioxide and titanium fluoride coatings to have a good barrier effect against acidic and alkaline substances, allowing the adhesive tape to withstand the erosion of sweat, sebum, and daily contact substances such as cosmetics, food and beverages, effectively reducing the damage of these substances to the performance of the adhesive tape and ensuring the long-term durability of the product.

[0023] 4. This solution achieves a lightweight design of the adhesive tape by optimizing the adhesive formula and support film material, reducing the thickness of the tape while ensuring the bonding performance, which is in line with the development trend of lightweight modern electronic products.

[0024] 5. The double-sided adhesive tape of the present invention is suitable for bonding the shell structure of handheld and wearable electronic products such as smart phones and smart watches. It can maintain stable sealing and bonding properties during long-term use and meet consumers' demands for product durability and protection. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] (1) Laying a polyethylene (PE) release film with a thickness of 12 μm on the working surface of a coating machine;

[0028] (2) In parts by mass, 18 parts of modified epoxy acrylate copolymer, 7 parts of nano boron nitride microsphere filler, 6 parts of silane-encapsulated cadmium oxide nanofiller, 0.2 parts of anti-ultraviolet stabilizer and 0.05 parts of nano silver ion antibacterial agent were added to a reaction kettle, stirred evenly and heated to 135° C., and high-shear mixed at 500 rpm to 850 rpm for 30 minutes to obtain an upper adhesive mixture; the upper adhesive mixture was coated on the upper release film to form an upper adhesive layer with a coating thickness of 10 μm; and then pre-dried at 80° C. for 15 minutes, secondary dried at 100° C. for 20 minutes, and final dried at 120° C. for 30 minutes were performed in sequence;

[0029] (3) preparing a fluorinated polyester (F-PET) support film layer with a thickness of 6 μm, uniformly distributing 6 parts of microsphere filler wrapped with tetraethyl lead in the support film layer by high shear stirring, and then performing fluorination pretreatment and nano-scale corona treatment on the surface of the support film layer, and then superimposing it on the surface of the upper adhesive layer;

[0030] (4) In parts by mass, 17 parts of fluorinated polyurethane acrylate copolymer, 12 parts of encapsulated thallium oxide microsphere filler, 0.1 parts of antioxidant, and 0.2 parts of fluorinated polydimethylsiloxane were added to a reaction kettle and stirred for 15 minutes, and high-sheared and uniformly dispersed at 1000 rpm for 40 minutes to obtain a lower adhesive mixture; the lower adhesive mixture was uniformly coated on the lower surface of the support film layer to form a lower adhesive layer with a thickness of 12 μm; and then pre-dried at 80° C. for 15 minutes, secondary dried at 90° C. for 30 minutes, and final dried at 100° C. for 45 minutes were performed in sequence;

[0031] (5) covering the surface of the lower adhesive layer with a polypropylene (PP) lower release film having a thickness of 10 μm;

[0032] (6) A 100 nm thick fluorinated silicon dioxide film is deposited on the outer surfaces of the upper and lower release films of the tape using PECVD technology, and then a 6 nm thick nano-titanium fluoride thin layer is deposited using plasma-assisted deposition; each layer is pre-dried at 70°C for 5 minutes after deposition, and finally dried at 150°C for 15 minutes to obtain a waterproof, sebum-resistant, and sweat-resistant pressure-sensitive double-sided adhesive tape.

[0033] Example 2

[0034] (1) Laying a polypropylene (PP) release film with a thickness of 15 μm on the working surface of a coating machine;

[0035] (2) Add 20 parts of modified epoxy acrylate copolymer, 5 parts of nano boron nitride microsphere filler, 10 parts of silane encapsulated cadmium oxide nanofiller, 0.2 parts of anti-ultraviolet stabilizer and 0.05 parts of nano silver ion antibacterial agent into a reaction kettle, stir evenly and heat to 130° C., gradually increase the speed to 800 rpm for high shear mixing at 500 rpm for 30 minutes to obtain an upper adhesive mixture; apply the upper adhesive mixture on the upper release film to form an upper adhesive layer with a coating thickness of 8 μm; then perform pre-drying at 80° C. for 10 minutes, secondary drying at 100° C. for 25 minutes, and final drying at 120° C. for 40 minutes in sequence;

[0036] (3) preparing a fluorinated polyester (F-PET) support film layer with a thickness of 7 μm, uniformly distributing 8 parts of microsphere filler wrapped with tetraethyl lead in the support film layer by high shear stirring, and then performing fluorination pretreatment and nano-scale corona treatment on the surface of the support film layer, and then superimposing it on the surface of the upper adhesive layer;

[0037] (4) In terms of mass fractions, 15 parts of fluorinated polyurethane acrylate copolymer, 13 parts of encapsulated thallium oxide microsphere filler, 0.1 parts of antioxidant, and 0.2 parts of fluorinated polydimethylsiloxane were added to a reaction kettle and stirred for 15 minutes, and high-sheared and uniformly dispersed at 1000 rpm for 40 minutes to obtain a lower adhesive mixture; the lower adhesive mixture was uniformly coated on the lower surface of the support film layer to form a lower adhesive layer with a thickness of 10 μm; and then pre-dried at 80° C. for 15 minutes, secondary dried at 90° C. for 40 minutes, and final dried at 100° C. for 60 minutes in sequence;

[0038] (5) covering the surface of the lower adhesive layer with a polyethylene (PE) lower release film having a thickness of 12 μm;

[0039] (6) A fluorinated silicon dioxide film with a thickness of 85 nm was deposited on the outer surfaces of the upper and lower release films of the tape using PECVD technology, and then a nano titanium fluoride thin layer with a thickness of 8 nm was deposited using plasma-assisted deposition; each layer was pre-dried at 70°C for 5 minutes after deposition, and finally dried at 150°C for 15 minutes to obtain a waterproof, sebum-resistant, and sweat-resistant pressure-sensitive double-sided adhesive tape.

[0040] Example 3

[0041] (1) Laying a polyethylene (PE) release film with a thickness of 10 μm on the working surface of a coating machine;

[0042] (2) In parts by mass, 15 parts of modified epoxy acrylate copolymer, 6 parts of nano boron nitride microsphere filler, 8 parts of silane-encapsulated cadmium oxide nanofiller, 0.2 parts of anti-ultraviolet stabilizer and 0.05 parts of nano silver ion antibacterial agent were added to a reaction kettle, stirred evenly and heated to 138° C., and high-shear mixed at 500 rpm to 850 rpm for 30 minutes to obtain an upper adhesive mixture; the upper adhesive mixture was coated on the upper release film to form an upper adhesive layer with a coating thickness of 12 μm; and then pre-dried at 80° C. for 20 minutes, secondary dried at 100° C. for 35 minutes, and final dried at 120° C. for 40 minutes were performed in sequence;

[0043] (3) preparing a fluorinated polyester (F-PET) support film layer with a thickness of 8 μm, uniformly distributing 5 parts of microsphere filler wrapped with tetraethyl lead in the support film layer by high shear stirring, and then performing fluorination pretreatment and nano-scale corona treatment on the surface of the support film layer, and then superimposing it on the surface of the upper adhesive layer;

[0044] (4) In parts by mass, 19 parts of fluorinated polyurethane acrylate copolymer, 11 parts of encapsulated thallium oxide microsphere filler, 0.1 parts of antioxidant, and 0.2 parts of fluorinated polydimethylsiloxane were added to a reaction kettle and stirred for 15 minutes, and high-sheared and uniformly dispersed at 1000 rpm for 40 minutes to obtain a lower adhesive mixture; the lower adhesive mixture was uniformly coated on the lower surface of the support film layer to form a lower adhesive layer with a thickness of 15 μm; and then pre-dried at 80° C. for 10 minutes, secondary dried at 90° C. for 15 minutes, and fixed dried at 100° C. for 30 minutes in sequence;

[0045] (5) covering the surface of the lower adhesive layer with a polypropylene (PP) lower release film having a thickness of 10 μm;

[0046] (6) A 90 nm thick fluorinated silicon dioxide film is deposited on the outer surfaces of the upper and lower release films of the tape using PECVD technology, and then a 7 nm thick nano-titanium fluoride thin layer is deposited using plasma-assisted deposition; each layer is pre-dried at 70°C for 5 minutes after deposition, and finally dried at 150°C for 15 minutes to obtain a waterproof, sebum-resistant, and sweat-resistant pressure-sensitive double-sided adhesive tape.

[0047] Example 4

[0048] (1) Laying a polyethylene (PE) release film with a thickness of 13 μm on the working surface of a coating machine;

[0049] (2) In parts by mass, 16 parts of modified epoxy acrylate copolymer, 5 parts of nano boron nitride microsphere filler, 9 parts of silane-encapsulated cadmium oxide nanofiller, 0.2 parts of anti-ultraviolet stabilizer and 0.05 parts of nano silver ion antibacterial agent were added to a reaction kettle, stirred evenly and heated to 130° C., and gradually increased the speed to 800 rpm for high shear mixing at 500 rpm for 30 minutes to obtain an upper adhesive mixture; the upper adhesive mixture was coated on the upper release film to form an upper adhesive layer with a coating thickness of 10 μm; and then pre-dried at 80° C. for 15 minutes, secondary dried at 100° C. for 25 minutes, and final dried at 120° C. for 30 minutes were performed in sequence;

[0050] (3) preparing a fluorinated polyester (F-PET) support film layer with a thickness of 7 μm, uniformly distributing 6 parts of microsphere filler wrapped with tetraethyl lead in the support film layer by high shear stirring, and then performing fluorination pretreatment and nano-scale corona treatment on the surface of the support film layer, and then superimposing it on the surface of the upper adhesive layer;

[0051] (4) In parts by mass, 15 parts of fluorinated polyurethane acrylate copolymer, 15 parts of encapsulated thallium oxide microsphere filler, 0.1 parts of antioxidant, and 0.2 parts of fluorinated polydimethylsiloxane were added to a reaction kettle and stirred for 15 minutes, and high-sheared and uniformly dispersed at 1000 rpm for 40 minutes to obtain a lower adhesive mixture; the lower adhesive mixture was uniformly coated on the lower surface of the support film layer to form a lower adhesive layer with a thickness of 10 μm; and then pre-dried at 80° C. for 20 minutes, secondary dried at 90° C. for 30 minutes, and final dried at 100° C. for 45 minutes were performed in sequence;

[0052] (5) covering the surface of the lower adhesive layer with a polyethylene (PE) lower release film having a thickness of 15 μm;

[0053] (6) A fluorinated silicon dioxide film with a thickness of 85 nm was deposited on the outer surfaces of the upper and lower release films of the tape using PECVD technology, and then a nano titanium fluoride thin layer with a thickness of 6 nm was deposited using plasma-assisted deposition; each layer was pre-dried at 70°C for 5 minutes after deposition, and finally dried at 150°C for 15 minutes to obtain a waterproof, sebum-resistant, and sweat-resistant pressure-sensitive double-sided adhesive tape.

[0054] Example 5

[0055] (1) Laying a polypropylene (PP) release film with a thickness of 10 μm on the working surface of a coating machine;

[0056] (2) In parts by mass, 19 parts of modified epoxy acrylate copolymer, 6 parts of nano boron nitride microsphere filler, 7 parts of silane encapsulated cadmium oxide nanofiller, 0.2 parts of anti-ultraviolet stabilizer and 0.05 parts of nano silver ion antibacterial agent were added to a reaction kettle, stirred evenly and heated to 140° C., and the mixture was gradually increased to 900 rpm at 500 rpm for high shear mixing for 30 minutes to obtain an upper adhesive mixture; the upper adhesive mixture was coated on the upper release film to form an upper adhesive layer with a coating thickness of 8 μm; and then pre-dried at 80° C. for 20 minutes, secondary dried at 100° C. for 30 minutes, and final dried at 120° C. for 40 minutes in sequence;

[0057] (3) preparing a fluorinated polyester (F-PET) support film layer with a thickness of 6 μm, uniformly distributing 5 parts of microsphere filler wrapped with tetraethyl lead in the support film layer by high shear stirring, and then performing fluorination pretreatment and nano-scale corona treatment on the surface of the support film layer, and then superimposing it on the surface of the upper adhesive layer;

[0058] (4) In parts by mass, 18 parts of fluorinated polyurethane acrylate copolymer, 10 parts of encapsulated thallium oxide microsphere filler, 0.1 parts of antioxidant, and 0.2 parts of fluorinated polydimethylsiloxane were added to a reaction kettle and stirred for 15 minutes, and high-sheared and uniformly dispersed at 1000 rpm for 40 minutes to obtain a lower adhesive mixture; the lower adhesive mixture was uniformly coated on the lower surface of the support film layer to form a lower adhesive layer with a thickness of 12 μm; and then pre-dried at 80° C. for 15 minutes, secondary dried at 90° C. for 20 minutes, and final dried at 100° C. for 30 minutes in sequence;

[0059] (5) covering the surface of the lower adhesive layer with a polyethylene (PE) lower release film having a thickness of 12 μm;

[0060] (6) A 120 nm thick fluorinated silicon dioxide film is deposited on the outer surfaces of the upper and lower release films of the tape using PECVD technology, and then a 5 nm thick nano-titanium fluoride thin layer is deposited using plasma-assisted deposition; each layer is pre-dried at 70°C for 5 minutes after deposition, and finally dried at 150°C for 15 minutes to obtain a waterproof, sebum-resistant, and sweat-resistant pressure-sensitive double-sided adhesive tape.

[0061] In summary, the test performance results of the above embodiments are shown in Table 1 below:

[0062] Table 1:

[0063]

[0064] Test description:

[0065] 1. Place the double-sided adhesive tape sample in 1 meter deep water and soak for 30 minutes, then take it out and test the adhesion strength retention rate (%). Retention rate = (adhesion strength after soaking / initial adhesion strength) × 100%. Each embodiment of the present invention shows excellent waterproof performance, especially embodiment 1 and embodiment 3, the adhesion strength retention rate reaches 98% and 97% respectively. In contrast, the retention rates of embodiment 4 and embodiment 5 are slightly lower, 95% and 94% respectively, but still meet the water resistance requirements and are suitable for environments with short-term contact with water.

[0066] 2. The double-sided adhesive tape samples were immersed in artificial sweat for 48 hours to simulate daily human contact, and then the adhesion strength retention rate was measured. Artificial sweat formulas usually contain NaCl, lactic acid and urea, etc., with a pH value between 4.3-4.5. All embodiments performed well in the sweat resistance test. The adhesion strength retention rates of Example 1 and Example 2 were 95% and 94%, respectively, which were better than other embodiments and showed stronger sweat resistance.

[0067] 3. The double-sided adhesive tape sample was placed in an artificial sebum solution and soaked for 48 hours, and the adhesion strength retention rate was tested after being taken out. The artificial sebum solution formula usually contains ingredients such as glycerol and fatty acids to simulate the influence of sebum on the material. The embodiments of the present invention all show good sebum resistance, especially embodiment 1 and embodiment 2, the adhesion strength retention rates in the sebum environment are 92% and 90% respectively. The sebum resistance of embodiments 3, 4, and 5 gradually decreases, but in the daily use environment of contact with sebum, it can still maintain a good bonding effect.

[0068] 4. The double-sided adhesive tape samples were immersed in pH 4 and pH 10 solutions for 48 hours, and then the adhesion strength retention rate was tested after removal. The pH 4 solution and the pH 10 solution simulate the daily contact environment of acidic and alkaline substances. All embodiments of the present invention show high acid-base tolerance, especially embodiment 1 and embodiment 2, with retention rates of 90% and 89% respectively. The acid-base tolerance of embodiment 5 is slightly lower, but it can still maintain a good bonding effect under certain acid-base conditions, and is suitable for the environment of daily contact with acid-base daily chemical products.

[0069] 5. The double-sided adhesive tape samples were soaked in artificial sweat for a long time, and their thickness change rate was measured regularly. The calculation formula was: thickness change rate = ((thickness after soaking - initial thickness) / initial thickness) × 100%. Examples 1 and 2 performed best in the thickness stability test, with thickness change rates less than 1%, indicating that the materials have high dimensional stability. The thickness change rates of Examples 3 and 4 were 2%, while the thickness change rate of Example 5 was slightly higher, at 3%, but it still maintained a relatively stable structure.

[0070] 6. The double-sided adhesive tape samples were exposed to artificial sweat for 72 hours, and the surface was observed for changes such as delamination and blistering. The stability of the sample appearance was recorded after the test. The appearance of Examples 1 and 2 did not change significantly after the test, showing a high appearance stability. Examples 3 and 4 showed slight delamination or blistering, while Example 5 showed obvious delamination under long-term exposure, indicating that it was slightly inferior to the previous examples in terms of appearance stability.

[0071] 7. Place the double-sided adhesive tape samples at room temperature, expose them to artificial sebum and artificial sweat for 90 days, and measure the adhesion failure rate of the samples. Failure rate = ((initial adhesion strength - adhesion strength after aging) / initial adhesion strength) × 100%. Example 1 has the lowest adhesion failure rate, about 2%, showing excellent durable adhesion performance. As the example number increases, the adhesion failure rate gradually increases, and the failure rate of Example 5 is 7%, showing that the adhesion durability decreases under longer-term exposure, but it can still meet daily bonding needs.

[0072] Test standard:

[0073] 1. Water resistance is based on the international standard ISO 62:2008 – Plastics – Determination of water absorption.

[0074] 2. Artificial sweat resistance is based on the international standard ISO 3160-2 – Metals and alloys in contact with the skin – Determination of corrosion resistance in artificial sweat.

[0075] 3. Sebum resistance is based on the international standard ISO 1817 – Vulcanized or thermoplastic rubber – Determination of the effects of liquids on materials.

[0076] 4. Acid and alkali resistance is based on the international standard ISO 175-Plastics-Determination of the effect of immersion in liquid chemicals.

[0077] 5. Dimensional stability is based on the international standard ISO 16770 – Determination of environmental stress cracking (ESC) of polyethylene – Full Notch Creep Test (FNCT).

[0078] 6. Appearance stability is based on the international standard ISO 2819-Chemical resistance evaluation-Appearance inspection method.

[0079] 7. Adhesion failure rate after aging is based on the international standard ISO 9142 - Adhesives - Guide for the selection of standard laboratory aging conditions for testing bonded joints.

[0080] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a waterproof, sebum-resistant and sweat-resistant pressure-sensitive double-sided adhesive tape, characterized in that: The steps include: (1) Lay the upper release film of polyethylene PE or polypropylene PP with a thickness of 10-15 μm on the working surface of the coating machine; (2) adding 15-20 parts by mass of a modified epoxy acrylate copolymer, 5-8 parts by mass of a nano boron nitride microsphere filler, 5-10 parts by mass of a silane-encapsulated cadmium oxide nanofiller, 0.2 parts by mass of an anti-ultraviolet stabilizer, and 0.05 parts by mass of a nano silver ion antibacterial agent to a reaction kettle, stirring evenly, heating to 130° C. to 140° C., and gradually increasing the speed to 800 rpm for high shear mixing at 500 rpm for 30 minutes to obtain an upper adhesive mixture; coating the upper adhesive mixture on an upper release film to form an upper adhesive layer with a coating thickness of 8-12 μm; and then pre-drying at 80° C. for 10-20 minutes, secondary drying at 100° C. for 15-35 minutes, and final drying at 120° C. for 20-40 minutes in sequence; (3) preparing a fluorinated polyester F-PET support film layer with a thickness of 6-8 μm, uniformly distributing 5-8 parts of tetraethyl lead-wrapped microsphere filler in the support film layer by high shear stirring, and then performing fluorination pretreatment and nano-scale corona treatment on the surface of the support film layer, and then superimposing it on the surface of the upper adhesive layer; (4) adding 15-20 parts by mass of fluorinated polyurethane acrylate copolymer, 10-15 parts of encapsulated thallium oxide microsphere filler, 0.1 parts of antioxidant, and 0.2 parts of fluorinated polydimethylsiloxane to a reaction kettle and stirring for 15 minutes, and uniformly dispersing at 1000 rpm for 40 minutes to obtain a lower adhesive mixture; uniformly coating the lower adhesive mixture on the lower surface of the support film layer to form a lower adhesive layer with a thickness of 10-15 μm; and then pre-drying at 80° C. for 10-30 minutes, secondary drying at 90° C. for 15-45 minutes, and final drying at 100° C. for 20-60 minutes in sequence; (5) Covering the surface of the lower adhesive layer with a polyethylene PE or polypropylene PP lower release film having a thickness of 10-15 μm; (6) A fluorinated silicon dioxide film is deposited on the outer surfaces of the upper and lower release films of the tape using PECVD technology, and then a nano-titanium fluoride thin layer is deposited using plasma-assisted deposition; each layer is pre-dried at 70°C for 5 minutes after deposition, and finally dried at 150°C for 15 minutes to obtain a waterproof, sebum-resistant, and sweat-resistant pressure-sensitive double-sided adhesive tape.

2. The method for preparing a waterproof, sebum-resistant and sweat-resistant pressure-sensitive double-sided adhesive tape according to claim 1, characterized in that: In the step (2), the particle size of the silane-encapsulated cadmium oxide nanofiller is 20-30 nm, and the anti-ultraviolet stabilizer is Benzotriazole.

3. The method for preparing a waterproof, sebum-resistant and sweat-resistant pressure-sensitive double-sided adhesive tape according to claim 1, characterized in that: In the step (3), the supporting film layer is a composition of a corona-treated fluorinated polyester F-PET and a tetraethyl lead microsphere filler.

4. The method for preparing a waterproof, sebum-resistant and sweat-resistant pressure-sensitive double-sided adhesive tape according to claim 1, characterized in that: In the step (4), the particle size of the encapsulated thallium oxide microsphere filler is 10-20 nm, and the antioxidant is Hindered Amine Light Stabilizer.

5. The method for preparing a waterproof, sebum-resistant and sweat-resistant pressure-sensitive double-sided adhesive tape according to claim 1, characterized in that: In the step (4), the fluorinated polyurethane acrylate copolymer is also subjected to graded viscous drying treatment in sequence, including pre-drying at 45° C. for 5-15 minutes, drying at 60° C. for 10-30 minutes and setting drying at 80° C. for 15-45 minutes.

6. The method for preparing a waterproof, sebum-resistant and sweat-resistant pressure-sensitive double-sided adhesive tape according to claim 1, characterized in that: In the step (6), the thickness of the fluorinated silicon dioxide film deposited by PECVD is 80-120 nm, and the thickness of the nano-titanium fluoride thin layer is 5-8 nm.

7. A waterproof, sebum-resistant, and sweat-resistant pressure-sensitive double-sided adhesive tape, made based on the method for preparing a waterproof, sebum-resistant, and sweat-resistant pressure-sensitive double-sided adhesive tape according to claims 1 to 6, characterized in that: The adhesive tape is composed of an upper release film, an upper adhesive layer, a PET film layer, a lower adhesive layer and a lower release film which are arranged in sequence.